When they marry Man was 30 year and 6month old.
And wife age was 15year and 3 month As given in the question that she is now in that year when her husband marry with her..
Now their ages is, Man is 60year6month old And
Wife is 30years 6 month old

As give in the their ages Total is 90
so
60+30=90years(in years)
6+6=12(in month)
12=1year
so
60+30+1=91

For easy understanding, here it is explained how to come to correct
answer:
Let husband’s age be x and wife’s y, therefore
x + y = 91 ……………………….. (1)
Situation as given in question is assumed to be n years before, so
x – n = y ………………………..(2)
x = 2(y – n) ………………………(3)
From (2), after substitution of (1) we get
x – n = 91 – x therefore 2x = 91 + n ………. (4)
Likewise from (3), after substitution of (2), we get
x = 2{(x – n) – n} or x = 2x – 2n – 2n or x = 2x – 4n
or x = 4n. Therefore, from (4), we get
2(4n) = 91 + n or 8n = 91 + n or 7n = 91 hence n = 13.
Thus, from (4), 2x = 91 + 13 gives us x = 52 and from (1)
we get y = 91 – 52 = 39.
This is my way of solving it.

x + y = 91
x = husband
y= wife
age of husband is twice , so
x=2y
put the value of x in the above equation,so
2y+y=91
3y=91
y=30.33
put the value of y in first equation
x +30.33 = 91
x=91-30.33
x=60.67
so
60.67+30.33=91
therefor
husband age = 60.67
wife age = 30.33

Husband’s Present age = 45.5 Years
Wife’s Present age = 34.125 Years
Wife’s age when Husband age was 34.125 Years = 22.75 Years
as first condition
45.5 + 2 (34.125-11.375) = 45.5 + 2 (22.75) = 45.5 + 45.5 = 91
and second condition
45.5 = 2 (34.125 – 11.375) = 2 (22.75) = 45.5
Both conditions satisfied

the husband age is 52 years old and the wife age is 39 years.

how it comes:- as the husband age and wife age is 91 years
the husband is twice wife age when he was as old as his wife
so the 91 -13 = 88 which is not suitable to be half husband age
at the time when he old as his wife, so 91-26=65 also not fit,so
91-39=52 which do the purpose

fatoyinbo juliet omololaMarch 21, 2012 at 3:58 PM#

I dont know the answer because i’m not good in maths. Meanwhile thanks sara for all the jokes God bless u.

correct answer ….. regardless the difference in the ages.
if his age now = twice her age when he was as old as she now
assuming her age = x thenhis age now = 2x
so… x + 2x = 91
3 x = 91
so x = 30.33 that mean her age will be 30 years and 4 months
and he will be 60 years & 8 months

correct answer ….. regardless the difference in the ages.
if his age now = twice her age when he was as old as she now
assuming her age = x thenhis age now = 2x
so… x + 2x = 91
3 x = 91
so x = 30.33 that mean her age will be 30 years and 4 months
and he will be 60 years & 8 months

i think you misunderstand the question.. read it again.. Hs2002ye is correct.
his age = y, her age =x
hers current age = before ‘ c ‘ his age
i.e x = y – c ——– (1)

his current age = twice her her age before ‘ c ‘ years
i.e y = 2 ( x – c )
=> y = 2( y – c – c )
y = 2y – 4c ——– (2)

we know x + y = 91 ——– (3)

substitute (1) & (2) in (3)

then, y – c + 2y – 4c = 91
=> 3y – 5c = 91 —— (4)

substitute (1) in (3)

then, (y – c) + y = 91
=> 2y – c = 91 —– (5)

(4) – (5),
you get y – 4c = 0 —— (6)

(5) – (6),
you get y + 3c =91 ——- (7)

(6) – (7),
you get ” c =13 ”

from (6), y = 4c
=> ” y = 52 ”
and obviously ” x = 39 ”

thats it…

(u people have got bored i think.. if u know any other simple method, let me knw plz )

Husband = 60 years and 8 months

wife= 30 years and 4 months

Husband’s age = 52

Wife’s age = 39

Wife: 30 years and four months

Husband: 60 years and eight months

Husband. 60yrs 8months

Wife. 30 yrs 4 months

Husband age 54 yrs 7.2 momths

Wife age. 36 yrs 4.8 months

to be honest, I didn’t understand the question properly.

Can you explain it a bit more?

Assume

Husbands age -a

Wifes age -b

Your Question 2a + b = 91, Divide 91 by 2 you get 45 Yrs 6 Mths which is c .,

the age for both at time of marriage : 1/3 value of c to wife = 15 Yrs 2 mths , 2/3 value to husband = 30 Yrs 4 mths

Present age of Husband : 60 Yrs 8 mths

Present age of Wife : 30 Yrs 4 mths

according to your answer, at the time of marriage,

wife age 15y 2m

and husband age is 30y 4m,

and now,

wife’s age is 30y 4 months

and husband’s age is 60y & 8m’s

How this is possible my friend?!

How many years have passed after their marriage???

Sara

Please after each riddle let us have the correct answer to guide against next time. Thank you for all the wonderful work you are doing

ok Lara.

Sure will try to give the answers.

But mostly people get the right answers in the comments as well.

husband 60 year 9 month

wife 30 year 3 month

Husband’s Age ( now ) : 60.67 Years

Wife’s Age ( now ) : 30.33 Years

is THE CORRECT ANSWER

When they marry Man was 30 year and 6month old.

And wife age was 15year and 3 month As given in the question that she is now in that year when her husband marry with her..

Now their ages is, Man is 60year6month old And

Wife is 30years 6 month old

As give in the their ages Total is 90

so

60+30=90years(in years)

6+6=12(in month)

12=1year

so

60+30+1=91

Now Proved it

Alhamdulilah

Nhree

nz

Great efforts Noor.

30 years and 4 month

30 years and 4 month

The husband age is 60years and 9 months.

And the wife is 30 years and 3 months

Sara, what is the answer?

For easy understanding, here it is explained how to come to correct

answer:

Let husband’s age be x and wife’s y, therefore

x + y = 91 ……………………….. (1)

Situation as given in question is assumed to be n years before, so

x – n = y ………………………..(2)

x = 2(y – n) ………………………(3)

From (2), after substitution of (1) we get

x – n = 91 – x therefore 2x = 91 + n ………. (4)

Likewise from (3), after substitution of (2), we get

x = 2{(x – n) – n} or x = 2x – 2n – 2n or x = 2x – 4n

or x = 4n. Therefore, from (4), we get

2(4n) = 91 + n or 8n = 91 + n or 7n = 91 hence n = 13.

Thus, from (4), 2x = 91 + 13 gives us x = 52 and from (1)

we get y = 91 – 52 = 39.

This is my way of solving it.

You are right of course.

When he was 26 she would have been 13, so he would have been twice her age when he was half his own age.

Using your method you can predict other numbers this will work with e.g. 75 and 99.

That is dogo turenchi. The woman is 30 years 4 months. Period!

x + y = 91

x = husband

y= wife

age of husband is twice , so

x=2y

put the value of x in the above equation,so

2y+y=91

3y=91

y=30.33

put the value of y in first equation

x +30.33 = 91

x=91-30.33

x=60.67

so

60.67+30.33=91

therefor

husband age = 60.67

wife age = 30.33

Inayat are you a Maths teacher?

Great Simultaneous equation. Well developed and solved. Thanks man!

It is Husband = 52 and wife = 39

husband present age = x

wife present age = 91-x

y year before, (x-y)=91-x

i.e, 2x-y=91 —– eqn 1

present condition, x=2[(91-x)-y]

i.e, 3x+2y=182 —–eqn2

solve eqn 1 and 2

x=52

y=13

thus, husband present age =52

wife present age 91-52= 39

A child asked his father, what would be 2 plus 3. his father answered, dont bring such a deficult questions to me, solve it by your teacher.

Help madam. I have already lost some hairs to get out from this riddle.

52+39 (if replied by the husband)

62+29 (if replied by the wife)

Husband’s Present age = 45.5 Years

Wife’s Present age = 34.125 Years

Wife’s age when Husband age was 34.125 Years = 22.75 Years

as first condition

45.5 + 2 (34.125-11.375) = 45.5 + 2 (22.75) = 45.5 + 45.5 = 91

and second condition

45.5 = 2 (34.125 – 11.375) = 2 (22.75) = 45.5

Both conditions satisfied

the husband age is 52 years old and the wife age is 39 years.

how it comes:- as the husband age and wife age is 91 years

the husband is twice wife age when he was as old as his wife

so the 91 -13 = 88 which is not suitable to be half husband age

at the time when he old as his wife, so 91-26=65 also not fit,so

91-39=52 which do the purpose

I dont know the answer because i’m not good in maths. Meanwhile thanks sara for all the jokes God bless u.

I ? != i

Big age diffrence ! Why did she marry him ! He must be rich lol

lol.

Husband is 52 yrs and wife is 39 yrs now

Correct Answer!!

HOW IT COME? IT SHOULD BE M= 60 YEAR AND 8 MONTH

F= 30 YEAR AND 4 MONTH

correct answer ….. regardless the difference in the ages.

if his age now = twice her age when he was as old as she now

assuming her age = x thenhis age now = 2x

so… x + 2x = 91

3 x = 91

so x = 30.33 that mean her age will be 30 years and 4 months

and he will be 60 years & 8 months

correct answer ….. regardless the difference in the ages.

if his age now = twice her age when he was as old as she now

assuming her age = x thenhis age now = 2x

so… x + 2x = 91

3 x = 91

so x = 30.33 that mean her age will be 30 years and 4 months

and he will be 60 years & 8 months

i think you misunderstand the question.. read it again.. Hs2002ye is correct.

his age = y, her age =x

hers current age = before ‘ c ‘ his age

i.e x = y – c ——– (1)

his current age = twice her her age before ‘ c ‘ years

i.e y = 2 ( x – c )

=> y = 2( y – c – c )

y = 2y – 4c ——– (2)

we know x + y = 91 ——– (3)

substitute (1) & (2) in (3)

then, y – c + 2y – 4c = 91

=> 3y – 5c = 91 —— (4)

substitute (1) in (3)

then, (y – c) + y = 91

=> 2y – c = 91 —– (5)

(4) – (5),

you get y – 4c = 0 —— (6)

(5) – (6),

you get y + 3c =91 ——- (7)

(6) – (7),

you get ” c =13 ”

from (6), y = 4c

=> ” y = 52 ”

and obviously ” x = 39 ”

thats it…

(u people have got bored i think.. if u know any other simple method, let me knw plz )

I think you need maths equations to solve this question.